Implementation of a Play-Based Approach to Improve Dribbling Skills in Physical Education Learning - Asrul, Muhammad; Bayu, Wahyu Indra; Gunawan, Gunawan (Bima Loka: Journal of Physical Education, 2025)
This study aimed to improve the dribbling skills of Grade VII.2 students at SMP Negeri 39 Palembang through the implementation of a game-based approach in physical education learning. The research employed Classroom Action Research (CAR) conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The participants were 32 students. Data were collected using a dribbling skill test and observation of student activities, while data analysis was carried out using descriptive quantitative methods by calculating mean scores and learning mastery percentages. The results indicated an improvement in students’ dribbling skills, as shown by an increase in the average score from 68.2 in the pre-cycle to 73.6 in Cycle I and further to 80.4 in Cycle II. The learning mastery percentage also increased from 31.25% in the pre-cycle to 56.25% in Cycle I and reached 81.25% in Cycle II. Therefore, it can be concluded that the game-based approach is effective in improving students’ dribbling skills in physical education learning at the junior high school level.